Taxonomy of the Genus Bryobia Koch (Acari: Tetranychidae): Reconsideration of Subgenera and Updated Species Groups - Jawwad Hassan Mirza; Fahad Jaber Alatawi; Muhammad Kamran; Carlos Holger Wenzel Flechtmann (Insects, 2024)
The present study aimed to revise the subgeneric divisions of the genus Bryobia based on persistent characteristics and to propose species groups in each subgenus to further ease the identification of species. As a result, only three subgenera, based on literature, are recognized, viz, subgenus Bryobia Koch (duplex setae present on leg tarsi III–IV), subgenus Allobia Livschits and Mitrofanov (duplex setae absent on leg tarsi III–IV), and subgenus Lyobia Livschits and Mitrofanov (duplex setae present only on leg tarsus III). The analysis based on morphological characters and available COI sequences on the GenBank database did not resolve the phylogenetic relationship of Bryobia species, and likewise, no support could be found for the proposed subgeneric divisions. The species in each subgenus were further categorized into species groups based on the position of the fourth pair of dorsocentral setae f1, viz, three species groups, praetiosa, osterloffi, and neoephedrae in subgenus Bryobia; three species groups, pritchardi, abbatielloi, and deserticola in subgenus Allobia; and three species groups, eurotiae, sarothamni, and rubrioculus in subgenus Lyobia. Furthermore, detailed notes are provided on eight Bryobia species which were described by Meyer, having morphological characteristics of both the tribes Bryobiini and Hystrichonychini. The generic status of two bryobine species, B. pseudorubrioculus Smiley and Baker and B. tuttlie Smiley and Baker, is also discussed and considered as species inquirendae.